Mengintegrasikan Agama, Filsafat, dan Sains - Nuraini Nuraini (Postgraduate Program Magister Pendidikan Agama Islam, 2017)
The effort of searching God that be done by human, some of them really find God but also many of them that be lost in the forest of Metafisisme. The discussion of philosophy and religion is the case that very interesting, even many philosophy which has been discussed about them, start from the contra until want to join both of them. In this case the contribution of philosophy and science is to accompany of faith to the God, within certain limits can support the various evidence of the truth of existence and the power of God which has been widely revealed by religion. Syari’at is the law of God, Which is not only legal that can’t be followed by philosophical reasoning. Islam came with the teachings, to be a fad for the people. In a definitive manner Syari’at become the way to face the God. Science and philosophy can move and grow because of the human mind and presence conviction. Science, philosophy or religion aims at least to deal with the same thing,that is the truth. However, the point of difference is in the source, science and philosophy sourced in ra’yu (mind of human). Whereas religion sourced in revelation. Science seek the truth by research, experience (empirical) and experiment as the exam. Philosophy approache the truth with exploration of common sense in radical (rooted), it does not feel bound by any, except by their own hands, that is logic. The human looking for and find the truth about religion by questioning of variety human problems or to scripture.